HUBUNGAN FUNGSI KELUARGA DENGAN TINGKAT STRES REMAJA DI MUHARTO RT 06 RW 13 KOTA MALANG: The Relationship Between Family Function and Adolescent Stress Levels in Muharto RT 06 RW 13 Malang City - Armince Nudi Tana; Yanti Rosdiana; Tantry Ajeng Parnawati (ASSYIFA : Jurnal Ilmu Kesehatan, 2024)
The incidence of stress in adolescents continues to increase, so supervision and assistance from both health and family parties is needed, one of which is the function of the family. The function of the family is as a prerequisite, reference and lifestyle for each family in order to create a harmonious family. The aim of the research is to determine the relationship between family function and adolescent stress levels in Muharto RT 06 RW 13 Malang City. The research design used cross sectional. The population of this study was 47 teenagers with a total sample of 47 teenagers. Samples were taken using total sampling technique. The independent variable is family function, the dependent variable is the development of stress levels. The instrument used was a questionnaire. Data analysis used the Spearman test. The results of this study show that the majority of teenagers in Muharto RT 06 RW 13 Malang City have adequate family functions (83.0%). Most teenagers in Muharto RT 06 RW 13 Malang City have moderate levels of stress (57.4%). There is a relationship between family function and adolescent stress levels in Muharto RT 06 RW 13 Malang City with a value of (p= 0.012). The correlation coefficient value r is 0.362, which shows that the relationship between family function and adolescent stress levels in Muharto RT 06 RW 13 Malang City is quite strong. It is hoped that future research will examine directly the general data of adolescent parents such as parental education, knowledge and family support as factors that can influence family functioning.